The International Atomic Energy Agency action plan on radiation protection of patients and staff in interventional procedures: Achieving change in practice. (August 2018) - Tsapaki, V.; Balter, S.; Cousins, C.; Holmberg, O.; Miller, D.L.; Miranda, P.; Rehani, M.; Vano, E.
Highlights: Manufacturers play an important role in making patients safer. Automatic patient dose (skin dose maps) reporting are essential for optimization. More studies on the impact of lens opacities in clinical practice. Paediatric patient dose data in interventional procedures are scarce. Abstract: Introduction: The International Atomic Energy Agency (IAEA) organized the 3rd international conference on radiation protection (RP) of patients in December 2017. This paper presents the conclusions on the interventional procedures (IP) session. Material and methods: The IAEA conference was conducted as a series of plenary sessions followed by various thematic sessions. "Radiation protection of patients and staff in interventional procedures" session keynote speakers presented information on: 1) Risk management of skin injuries, 2) Occupational radiation risks and 3) RP for paediatric patients. Then, a summary of the session-related papers was presented by a rapporteur, followed by an open question-and-answer discussion. Results: Sixty-seven percent (67%) of papers came from Europe. Forty-four percent (44%) were patient studies, 44% were occupational and 12% were combined studies. Occupational studies were mostly on eye lens dosimetry. The rest were on scattered radiation measurements and dose tracking. The majority of patient studies related to patient exposure with only one study on paediatric patients. Automatic patient dose reporting is considered as a first step for dose optimization. Despite efforts, paediatric IP radiation dose data are still scarce. The keynote speakers outlined recent achievements but also challenges in the field. Forecasting technology, task-specific targeted education from educators familiar with the clinical situation, more accurate estimation of lens doses and improved identification of high-risk professional groups are some of the areas they focused on. Conclusions: Manufacturers play an important role in making patients safer. Low dose technologies are still expensive and manufacturers should make these affordable in less resourced countries. Automatic patient dose reporting and real-time skin dose map are important for dose optimization. Clinical audit and better QA processes together with more studies on the impact of lens opacities in clinical practice and on paediatric patients are needed.